Education Of Competencies Of Organic Production: Possibilities And Problems (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Organic farming must seek profitability, social goals and ecological balance. Not only farmers and processors but also consumers are responsible for this, subsequently, education of every segment is very important. In order to modernize technologies of organic farming it is necessary to have qualified and experienced employees for industrial areas as well as for organisation of environmental protection. The article is trying to assess development of organic farming and to evaluate education of specialists of organic production in Lithuania. Therefore, there are analysed the results of certification of farms, carried out by the public organisation “Ekoagros”, and a particular interest is paid to educational establishments which educate specialists of organic production. The article also analyses development of organic farms in Lithuania, presents basic problems and examines possibilities to educate specialists of organic agricultural production.